The interactional architecture of the language classroom : a conversation analysis perspective - Seedhouse, Paul. (Malden, MA : Blackwell Publishing, 2004)
This volume explains the basic principles of conversation analysis and studies its relevance to second language learning.
Includes bibliographical references and index.
Keywords: Conversation analysis; Discourse analysis; Oral communication; Language arts; Interaction analysis in education; Second language acquisition